Dual-energy CT of the urinary tract. - Kaza RK; Platt JF; Megibow AJ; Kaza, Ravi K; Platt, Joel F; Megibow, Alec J (Abdominal Imaging, 2013)
With the ability to provide structural- and material-specific information with single phase of image acquisition, dual-energy CT has several useful applications in urinary tract imaging such as evaluation of renal mass, CT urography, and characterization of urinary calculi. Although the underlying principle of dual-energy scanning is similar, there are several important differences in the currently available dual-energy scanners and the image processing algorithms used for these scanners. Knowledge of the principle of dual-energy data acquisition and image processing is essential to understand the advantages and limitations of dual-energy CT in urinary tract imaging.